Exploring the adoption of sustainable omni‑channel grocery technologies among Generation Z in Malaysia: The moderating role of risk mitigation for perishability - Nornajihah Nadia Hasbullah; Ag Kaifah Riyard Kifee; Hainnuraqma Rahim; Fathimath Zaina Shahid; Saiful Anwar; K. K. Ramachandran (Springer Nature Switzerland AG, 2025)
Advancements in technology have allowed businesses in Malaysia to shift from a multi-channel strategy to an omni-channel approach. Despite this change, there have been limited studies on Malaysian consumers' readiness to embrace omni-channel retailing, specifically grocery shopping. Moreover, the idea of a seamless shopping experience across different channels is relatively new in Malaysia. This research confirmed the legitimacy of UTAUT2 in omni-channel grocery retailing, taking into account risk mitigation of product perishability as a factor affecting customer purchase intention. The survey included 250 Generation Z respondents, with data analysis conducted using partial least squares–structural equation modelling (PLS-SEM). Unlike past research, the direct correlation showed that performance expectancy and facilitating conditions were the only factors that had a significant connection with omni-channel grocery buying intention. The moderating effect showed that risk mitigation for perishable product only significantly interacts with effort expectancy and price in relation to omni-channel grocery purchase intention. The research provides both theoretical and practical knowledge on Generation Z customers' preparedness for using technology in omni-channel grocery shopping. Furthermore, this research offered helpful recommendations for retailers who use omni-channel strategies to develop their omni-channel customer base.